2003
DOI: 10.1021/jp027038d
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Photochemistry and Photodynamics of the Chromophore of Green Fluorescent Protein (GFP)

Abstract: Hole-burning and temperature-dependent spectroscopy in green fluorescent protein (GFP) have been shown in the literature to be valuable tools in unraveling the photodynamics of this protein. It would be straightforward to perform similar experiments on the isolated GFP chromophore to differentiate between properties that are affiliated with the chromophore itself and those that are rather determined by the protein cage. To this end, we performed temperature-dependent and hole-burning spectroscopy on the organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…8 These observations were attributed to the inhibition of rapid internal conversion involving motion with considerable amplitude. It was established 55 that the free chromophore in low-temperature alcoholic solution shows a spectral and photochemical reaction pattern similiar to that of the chromophore embedded in the protein matrix. In a poly(vinyl alcohol) (PVA) matrix, even ESPT is recoverd (P. Schellenberg, private communication).…”
Section: Contributions To Ground-state Equilibriamentioning
confidence: 99%
“…8 These observations were attributed to the inhibition of rapid internal conversion involving motion with considerable amplitude. It was established 55 that the free chromophore in low-temperature alcoholic solution shows a spectral and photochemical reaction pattern similiar to that of the chromophore embedded in the protein matrix. In a poly(vinyl alcohol) (PVA) matrix, even ESPT is recoverd (P. Schellenberg, private communication).…”
Section: Contributions To Ground-state Equilibriamentioning
confidence: 99%
“…Green fluorescent protein (GFP) is an important fluorescent marker in cell biology, exhibiting a complex photophysics and photochemistry that has been the subject of many investigations during the last 10 years . Experimental as well as theoretical works have been mainly devoted to shedding light into the complex photophysics of the protein, arising from the internally caged chromophore and the nearby residues. A great part of the interest on GFP comes from the multiple proton relay system that operates in it after photoexcitation.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies on the photophysics and photochemistry of GFP are usually interested in the overall cycle occurring upon photon absorption. The number of experiments concerning the three-step proton wire operating inside the protein is enormous, whereas there is comparatively less theoretical work on the simulation and modeling of the three proton-transfer processes that constitute the photoactivated proton wire. Some theoretical studies have focused on the nonradiative deactivation pathways of the photoexcited chromophore, , involving mainly bond torsions that lead to a loss of planarity.…”
Section: Introductionmentioning
confidence: 99%
“…We will return to the viscosity dependence below. Other groups have investigated the spectroscopy of compounds similar to I as models for GFP spectroscopy. In particular Schellenberg and co-workers have demonstrated that there are significant differences in the Raman spectra of I and GFP, while I has a low-temperature photochemical hole-burning behavior which is rather similar to that observed in GFP. , …”
Section: Introductionmentioning
confidence: 99%